The Role of Artistic Expression in Therapeutic Design - Davies, Alexis M. (My University, 2024)
Over my years at Kansas State University pursuing my master’s in interior architecture, I have realized that my design philosophy revolves around human connection and expression. I aspire to design spaces that are artistic and inclusive while placing value on well-being. To implement and represent this concept, my thesis looks to struggles of occupational stress and self-expression, both of which are key professional problems present and relevant to today. Throughout this research, design development, and final proposal, I seek to design a therapeutic space that hinges on creative expression through the practice of art therapy. In the design of this interior build-out, I hope to showcase my interior architecture, furniture, and graphic design knowledge and versatility.